Regional Variation in Identified Cancer Care Needs of Early-Career Oncologists in China, India, and Pakistan. (17th April 2015) - Lyerly, H. Kim; Fawzy, Maria R.; Aziz, Zeba; Nair, Reena; Pramesh, C.S.; Parmar, Vani; Parikh, Purvish M.; Jamal, Rozmin; Irumnaz, Azizunissa; Ren, Jun; Stockler, Martin R.; Abernethy, Amy P.
Abstract: Background: Cancer incidence and mortality is increasing in the developing world. Inequities between low-, middle-, and high-income countries affect disease burden and the infrastructure needs in response to cancer. We surveyed early-career oncologists attending workshops in clinical research in three countries with emerging economies about their perception of the evolving cancer burden. Methods: A cross-sectional survey questionnaire was distributed at clinical trial concept development workshops held in Beijing, Lahore, Karachi, and Mumbai at major hospitals to acquire information regarding home-country health conditions and needs. Results: A total of 100 respondents participated in the workshops held at major hospitals in the region (India = 29, China = 25, Pakistan = 42, and other = 4). Expected consensus on many issues (e.g., emergence of cancer as a significant health issue) was balanced with significant variation in priorities, opportunities, and challenges. Chinese respondents prioritized improvements in cancer-specific care and palliative care, Indian respondents favored improved cancer detection and advancing research in cancer care, and Pakistani respondents prioritized awareness of cancer and improvements in disease detection and cancer care research. For all, the most frequently cited opportunity was help in improving professional cancer education and training. Conclusion: Predominantly early-career oncologists attending clinical research workshops (in China, India, and Pakistan) identified needs for increasing clinical cancer research, professional education, and public awareness of cancer. Decision makers supporting efforts to reduce the burden of cancer worldwide will need to factor the specific needs and aspirations of health care providers in their country in prioritizing health policies and budgets. Abstract : A cross-sectional survey questionnaire was distributed at clinical trial concept development workshops held at major hospitals in Beijing, Lahore, Karachi, and Mumbai to acquire information regarding home-country health conditions and needs. The respondents were predominantly early-career oncologists who identified needs for increasing clinical cancer research, public awareness of cancer, and especially professional cancer education and training.